RANCANG BANGUN SISTEM MONITORING KINERJA MOTOR SERVO DAN JUMLAH PAKAN PADA ALAT PAKAN IKAN BERBASIS INTERNET OF THINGS (IoT) - yuniarti, erliza; Sofiah, Sofiah; Hidayat, Ridho (Universitas PGRI Palembang, 2022)
Technological advances have an impact on the manufacture of devices that really help daily activities. Utilization of technological advances, especially for cultivation, is useful for increasing productivity, facilitating cultivation and efficiency of operational costs. This automatic animal feed tool designed with an automatic control system is a prototype for a working system for controlling fish feed in a pond. This study aims to design an internet of things (IoT) based automatic animal feeder with servo motor performance monitoring. The performance test of the designed tool is carried out with variations in the feed load used, to be the basis for setting the timer to activate the servo motor. Monitoring the electric current and voltage in the feeding equipment can be carried out properly, with a maximum working voltage of 223.76 Volts and current. 0.06 Ampere on feeding with a weight of 200 grams.